Cross-dressing and sex change stories in Spanish illustrated magazines (1928–1936). Issue 2 (4th May 2019) - Cruz-Cámara, Nuria
ABSTRACT: During the 1920s and 1930s, the impression that the boundaries between the sexes were increasingly blurring was pervasive in many parts of the world. In Spain, sexual ambiguity often became the focus of public discussions on the upheaval of the traditional gender order. As part of this phenomenon, stories of cross-dressers made good copy in popular illustrated magazines such as Nuevo Mundo, Mundo Gráfico, Estampa, and Crónica, which were the top-sellers of their kind during the interwar period. By analyzing a group of cross-dressing and sex change stories from these periodicals – the way they were told and interpreted – I shed light on the ways in which the perceived fluidity of gender was constructed in a medium that reached a relative large segment of the Spanish population. The journalistic pieces I consider manifested different reactions to sexual ambiguity that ranged from the condemnatory to the matter-of-fact. Regardless, they all contributed – implicitly or explicitly – to undermine essentialist arguments underpinning the ideology of separate spheres of action for men and women. On occasion, these texts put forth an intimation, avant la lettre, of Judith Butler's notion of the performativity of gender.